2011
DOI: 10.1002/pmic.201100193
|View full text |Cite
|
Sign up to set email alerts
|

Detecting protein complexes and functional modules from protein interaction networks: A graph entropy approach

Abstract: Recent high‐throughput experiments have generated protein–protein interaction data on a genomic scale, yielding the complete interactome for several organisms. Various graph clustering algorithms have been applied to protein interaction networks for identifying protein complexes and functional modules. Although the previous algorithms are scalable and robust, their accuracy is still limited because of the complex connectivity found in protein interaction networks. In this study, we propose a novel information‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 48 publications
1
40
0
Order By: Relevance
“…With the integration of network entropy index, the MDv value used for on‐module identification was considered a more stringent criterion, so fewer on‐modules were identified by MDv, but the reduced entropy represented better modular structure . According to the MDv value, the on‐modules and characteristic UAMs of different drugs may help to elucidate their specific or unique actions.…”
Section: Discussionmentioning
confidence: 99%
“…With the integration of network entropy index, the MDv value used for on‐module identification was considered a more stringent criterion, so fewer on‐modules were identified by MDv, but the reduced entropy represented better modular structure . According to the MDv value, the on‐modules and characteristic UAMs of different drugs may help to elucidate their specific or unique actions.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, most of the prominent graph clustering algorithms, such as MCODE [44] and CFinder [20], failed in running with the genome-wide human PPI network that we use. We were thus able to receive the clustering results from two algorithms, Markov Clustering (MCL) [45] and Graph Entropy algorithm [46]. When the clustering results from MCL and Graph Entropy were compared to the integrated reference data set of human protein complexes, we had recall in the range between 0.4 and 0.45 and precision in the range between 0.4 and 0.52 as shown in Table III, which are lower than our network alignment results in Table II.…”
Section: Prediction Accuracy Of Network Alignment By Semantic Mappingmentioning
confidence: 99%
“…It has been observed that PPI networks are typically modular [3]. Consequently, various graph clustering algorithms [4], [5] have been applied to the networks for the purpose of identifying protein complexes and functional modules. A protein complex consists of proteins that interact at the same time and same place, building a larger molecular machine.…”
Section: Introductionmentioning
confidence: 99%